Size dependent toxicity of zinc oxide nano-particles in soil nematode Caenorhabditis elegans. Issue 4 (May 2015) - Khare, Priyanka; Sonane, Madhavi; Nagar, Yogendra; Moin, Nida; Ali, Shakir; Gupta, Kailash Chand; Satish, Aruna
Abstract Zinc oxide nano-particles (ZnO NPs), with their unique physico-chemical properties conferred by various size formulations, are extensively used in consumer products. The enormous usage coupled with their release to the environment demands risk assessment of ZnO NPs on health and the environment. Toxicity of ZnO NPs is well understood in comparison to the bulk ZnO. However, toxicity in relation to the NP size is poorly understood. In this context, we examined the adverse effects of different sizes (35 nm, 50 nm and 100 nm) of ZnO NPs in soil nematode C. elegans along with bulk ZnO and ZnCl2. Here, we show that growth, reproduction and behavior of worms were adversely affected by ZnO NPs in a size dependent manner. Further, exposure to ZnO NPs caused modulation of expression/function of genes associated with Insulin/IGF-like signaling pathway and/or stress response pathway in a size dependent manner in exposed worms. The expression of pro-apoptotic gene and suppression of anti-apoptotic genes, together with increased numbers of cell corpses in the germ line, indicated that apoptosis was also dependent on the size of the ZnO NP. Taken together, our study provides evidence that exposure to ZnO NPs disrupts various physiological processes and causes apoptosis in the germ-line even at very low concentration in a size dependent manner. Our finding suggests the inclusion of size as an additional measure for the cautious monitoring of ZnO NP disposal into the environment.